Double Decolonization: Bridging East Asia and Religious Studies in a Post-COVID World - Guo, Ting (Implicit Religion, 2024)
Following the outbreak of COVID-19, there emerged a popular narrative that East Asians are submissively complying control measures because they have been conditioned by Confucianism. Taking this narrative as a point of departure, this article reflects on why and how East Asia has been essentialized as a historical and distant other and left out of post-decolonial conversations from a religious studies perspective. Proposing a framework of “double decolonization,” the article historicizes the co-production of such orientalist narrative by both global and regional hegemonies for nationalistic, imperialistic, or other ideological reasons, hence the need to double-decolonize such essentialization. Furthermore, this article emphasizes the diffused and socially engaged nature of East Asia religions against acontextual imaginations underlying the World Religions Paradigm (WRP) and introduces the notion of “transnationally Asian” to highlight the transnational nature of local hegemonies and the transnational formation of agency against such hegemonies.